Pemboikotan Ekonomi Terhadap Produk Non-Muslim Perspektif Hukum Islam - Lahaddese, Idrus Abidin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2023)
Economic boycotting in Islam is a policy adopted by a prominent member of the Muslim community, a leader of an Islamic institution, or a ruler of a Muslim state to refrain from economic interaction with non-Muslims based on mutual agreement between the aggrieved parties with the intention of pressuring the non-Muslims to change their political stance on a specific issue. This research uses a qualitative approach and a literature review analysis method. The researcher seeks primary data and secondary data. The primary data in this study are academic works on the authenticity of economic boycotting based on Islamic law. Meanwhile, the secondary data comprises supporting research such as Maslahah Mursalah from books, journals, and seminar results that are pertinent to the study theme. Because, in essence, the study of economic boycotting of non-Muslim economic products in Islamic legal discourse falls within the category of neutral benefit (mursalah) that is neither explicitly legalized by Allah (gairu mut'tabarah) nor clearly annulled (gairu mulgah). Therefore, to implement this boycott law, an in-depth study is required to determine which is more beneficial, whether to boycott or not. The results of the study indicate that economic boycott against non-Muslim products is only temporary, so it does not apply indefinitely. The boycott only serves as a shock therapy; if the economic boycott is effective and the boycotted party has changed their attitude in accordance with normal conditions, then the Muslim party's economic relations with non-Muslim economic products will automatically resume.